When a Woman Ascends the Stairs - Naruse, Mikio; Tamai, Masao; Takamine, Hideko; Mori, Masayuki; Dan, Reiko
An attractive widow is forced to make a living as a bar hostess in this Japanese classic, finally released in the UK. Made in 1960, it's an involving portrait of a strong woman, Keiko, who is weighing up her options - open her own bar or find a husband? Each choice has its pitfalls in this leisurely but rewarding black and white melodrama, which gives a fascinating insight into the Tokyo of decades gone by. [www.bbc.co.uk]
Keywords: DVD-Video